2020
DOI: 10.1111/ibi.12830
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of habitat characteristics and co‐occurrence with closely related species on occupancy of resident ‘wood‐warblers’ in a Neotropical working landscape

Abstract: The simultaneous effects of habitat traits and interspecific interactions determine the occurrence and habitat use of wildlife populations. However, little research has been devoted to examining spatial co‐occurrence among closely related species while considering the effect of habitat variation and imperfect detectability of species in the field. In this study, we focused on migratory and resident 'wood‐warblers' that coexist during the winter in a Neotropical working landscape in southern Mexico to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Evidence from community niche partitioning at overwintering and stopover sites suggests that rather than maintain niches overlapped by migrants, resident species plastically shift their niches to alleviate competition during periods when migrants are abundant (Jedlicka et al., 2006; Waide, 1981). When coexisting with migrants, resident species display ecological shifts in foraging niches (Jedlicka et al., 2006), minimal overlap in diet (Poulin & Lefebvre, 1996), spatial segregation via microhabitat selection (Bensusan et al., 2011; Ortega‐Álvarez et al., 2020), and increases in territorial and calling behavior (Bensusan et al., 2011). Similarly, breeding species that share tightly packed areas of signal space with migrants (Figure 3) could partition the acoustic resource via spatial and/or temporal avoidance (Planqué & Slabbekoorn, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from community niche partitioning at overwintering and stopover sites suggests that rather than maintain niches overlapped by migrants, resident species plastically shift their niches to alleviate competition during periods when migrants are abundant (Jedlicka et al., 2006; Waide, 1981). When coexisting with migrants, resident species display ecological shifts in foraging niches (Jedlicka et al., 2006), minimal overlap in diet (Poulin & Lefebvre, 1996), spatial segregation via microhabitat selection (Bensusan et al., 2011; Ortega‐Álvarez et al., 2020), and increases in territorial and calling behavior (Bensusan et al., 2011). Similarly, breeding species that share tightly packed areas of signal space with migrants (Figure 3) could partition the acoustic resource via spatial and/or temporal avoidance (Planqué & Slabbekoorn, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The Yellow-rumped Warbler is a habitat specialist within its breeding grounds, but it is more generalist and tolerant to anthropogenic disturbances during migration. 20,25 We suggest that such tolerance might be heavily mediated by urban trees, given that they provide exceptional feeding resources for those birds that are able to cope with urban anthropogenic disturbances. 45 We observed that other substrates (e.g.…”
Section: Sitesmentioning
confidence: 99%
“…chasing competitors and patrolling feeding areas) during both the breeding and migratory seasons, particularly when food is scarce 24 ; still, it gathers in single-and mixed-species flocks during the winter. 25,26 The density of the Yellow-rumped Warbler is variable among sites throughout its breeding range, and it has been poorly assessed across its wintering grounds. 20 Despite being common, 19,21 little research has been performed on this species, and further evaluations are needed to increase our comprehension about the effects of human activities on its populations.…”
Section: Study Speciesmentioning
confidence: 99%